Ch3 U-Pb Detrital Zircon Geochronology Datasets - Wai Kehadeezbah Allen (2024)
This file contains all U-Pb zircon geochronology results collected at the University of Arizona - Laserchron Center and Washington State University Detailed datasets include laser settings and counts per second for each analysis See summary for all U-Pb detrital zircon analyses for GPS, geographic location, and sample name. This data table can be used for guidance to each raw dataset. Additionally, summary datatable files are grouped into Western, Central, and Eastern Stratigraphic packages. Information sheets provide additional information for U-Pb methods. Samples: FTUPbICP-1248-1, FTUPbICP-1248-2, FTUPbICP-1248-3 are samples analyzed at Washington State University for Jeffrey Benowitz All other samples were analyzed at the University of Arizona Laserchron Center ( NSF-EAR 1649254 )